ANALYSIS OF BPJS PARTICIPANTS’ SATISFACTION WITH SERVICES AT KLINIK PRATAMA ARINDA MEDIKA - Lina Contesa (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2026)
The quality of health services are important issues within the National Health Insurance system administered by BPJS Kesehatan, where patient satisfaction serves as a key indicator of service quality. This study aimed to analyze BPJS participants’ satisfaction with services at Arinda Medika Primary Clinic Palembang City. This study used a quantitative analytic descriptive design with a cross-sectional approach. The population consisted of 112 participants and the sample consisted of 40 respondents selected using accidental sampling. Data were collected using a SERVQUAL-based questionnaire covering tangible, reliability, responsiveness, assurance, and empathy dimensions, and were analyzed using univariate and bivariate analysis with the chi-square test. The results showed that most respondents rated service quality as good (70.0%) and the majority were satisfied (65.0%). Statistical analysis indicated a significant relationship between service quality and BPJS participant satisfaction (p = 0.012). It is concluded that service quality influences patient satisfaction; therefore, continuous improvement of service quality is necessary to enhance BPJS participant satisfaction.